PERENCANAAN PEMBIAYAAN PENDIDIKAN (Studi Kasus di Sekolah Dasar) - K, Dedy Achmad (PEDAGOGIA, 2014)
Financial planning education, especially regarding the analysis of the needs of education ( elementary school ) in the future should be able to run, so that the achievement of the plancan be realized well with effective management and efficient budget . Educational arrangements referred to in this article is how governments , agencies or schools can plan sees the need for schools , classrooms and teachers in the community standard which is based on meeting the minimum standards of education . The aim is to assist in the distribution of education and know the real condition of the school in the community . Schools targetedmainly primary school level are included in compulsory education launched by the government .Keywords : Planning , Financing , Budgeting and Mapping Guru